CNC Plotter Core XY Tipe H-Bot Sebagai Alat Drawing Dengan Akurasi Tinggi - M, Muas; Salam, Abdul; Fair, Ariel; Alim Tammah, Farhan; Zhulfiadi Rahman, Muh (Jurnal Teknik Mesin Sinergi, 2026)
The rapid development of manufacturing and creative industries requires high-precision and efficient digital fabrication tools. One of the technologies widely used to support automated drawing and prototyping processes is the Computer Numerical Control (CNC) plotter. However, conventional CNC plotters often experience limitations related to motion stability, positioning accuracy, and repeatability due to the inertia of the gantry mechanism. This research aims to design and develop a CNC plotter based on the Core XY H-Bot mechanism to improve motion stability and drawing accuracy. The system was designed using a belt-driven Core XY H-Bot configuration with two NEMA 17 stepper motors controlled by an Arduino Uno and CNC Shield using modified GRBL firmware. The mechanical structure utilizes stainless steel shafts, GT2 timing belts, and 3D printed components. Experimental testing was conducted to evaluate system accuracy and repeatability by comparing programmed G-code commands with the actual movement of the drawing tool. The results show that the developed CNC plotter achieved an accuracy level of 99.04%, with a repeatability deviation of 0.219 mm and an optimal feed rate of 800 mm/min. These results indicate that the Core XY H-Bot mechanism provides stable motion and sufficient precision for drawing applications and educational purposes. The proposed system offers a cost-effective and efficient solution for developing high-precision CNC plotter systems.